A study on awareness level of wind disaster - Nur Afiqah, Mohd Yusop (2014)
Recently the numbers of damage and injuries due to wind disaster in the past few years had increased in Malaysia. However, many people do not concert about the effect or impact that would happen if the wind disaster occurs. This is because when a situation arises, the Malaysian people are not aware of the dangers of wind. Most of possibility risk of the wind disaster potentially damaging physical event, phenomenon or human activity that may cause the loss of life or injury, property damage, social and economic disruption or environmental degradation in Malaysia is due to a thunderstorm or windstorm. The losses caused by a typical damage value. This paper propose about the wind disaster effect among people in Malaysia and the awareness level of the wind disaster between two categories which is a public and government sector. Furthermore, public awareness and understanding about the wind disaster is very important as a precautionary measure from wind disaster occur. Demographic data can be used as an input in systematic study to know about the effect, prepared to face this situation and to know about how many people in Malaysia may concern about wind disaster if this disaster occur. From the data that has done through a review of the questionnaire, the respondents said that they are increasingly aware of the catastrophic effects of wind. So, it can be concluded that the goal of this study was to analyze the level of disaster awareness wind and wind effects disaster in Malaysia which has been achieved.